STUDI KOMPARATIF PEMBELAJARAN KOOPERATIF DAN PEMBELAJARAN KONVENSIONAL DALAM MENINGKATKAN HASIL BELAJAR IPAS MATERI GAYA SISWA KELAS IV SDI KUANINO 3 - Deni Aryanto Baitanu; Heryon Bernard Mbuik; Yulsy Marselina Nitte (STKIP Subang, 2026)
This research is motivated by the low learning outcomes of students in the Natural and Social Sciences (IPAS) subject of style material in grade IV of SDI Kuanino 3, which is caused by the use of conventional learning models that do not actively involve students. This study aims to determine the difference in effectiveness between cooperative learning and conventional learning in improving student learning outcomes. The method used is quantitative research with a quasi-experimental design. The research population amounted to 32 students who were divided into two groups, namely the experimental class (16 students) who used cooperative learning and the control class (16 students) who used conventional learning. The data collection technique uses tests (pretest and posttest), while data analysis uses t-test. The results showed that the average posttest score of the experimental class was 89.50 higher than the control class of 68.19. The results of the hypothesis test showed that the significance value of 0.000 < 0.05 and the value of t-count (-13.430) was greater than the t-table (2.042), so that H₀ was rejected and Hₐ was accepted. Thus, it can be concluded that cooperative learning is more effective than conventional learning in improving the learning outcomes of social studies style material for grade IV students of SDI Kuanino 3.